Soft HRM and work environment for elevating job satisfaction of employees: redefining the validated model of private sectors for Generation Y - Islam S.N.; Bahar A.K.M.M.; Jambulingam M.; Hassan M.D.M.; Alam M.N. (Inderscience Publishers, 2023)
The objectives of the study were to explore the necessity of soft HRM and work environment for job satisfaction of employees in the private sector. Generation Y has a general trend of quitting the job if they are not satisfied with their profession. Frequent turnover becomes one of the leading debates in the non-western region as well as in developing countries like Bangladesh. The study used Smart (PLS) to scrutinise the data, create the model, and sort out the mediating impacts of work environment between soft HRM (SHRM) and job satisfaction. The field theory, social exchange theory, and HRM models served as the foundation for the study. The result shows that soft HRM has significant positive effects on job satisfaction mediating through the work environment. The study enhances the existing literature and practically helps the HR practitioners against the lack of job satisfaction. Copyright 2022 Inderscience Enterprises Ltd.